Genotypic Characterization of Salmonella typhi by Amplified Fragment Length Polymorphism Fingerprinting Provides Increased Discrimination as Compared to Pulsed-Field Gel Electrophoresis and Ribotyping - Nair, S.; Schreiber, E.; Thong, Kwai Lin; Pang, T.; Altwegg, M. (2000)
Amplified fragment length polymorphism (AFLP) is a recently developed, PCR-based high resolution fingerprinting method that is able to generate complex banding patterns which can be used to delineate intraspecific genetic relationships among bacteria. In the present study, AFLP was evaluated for its usefulness in the molecular typing of Salmonella typhi in comparison to ribotyping and pulsed-field gel electrophoresis (PFGE). Six S. typhi isolates from diverse geographic areas (Malaysia, Indonesia, India, Chile, Papua New Guinea and Switzerland) gave unique, heterogeneous profiles when typed by AFLP, a result which was consistent with ribotyping and PFGE analysis. In a further study of selected S. typhi isolates from Papua New Guinea which caused fatal and non-fatal disease previously shown to be clonally related by PFGE, AFLP discriminated between these isolates but did not indicate a linkage between genotype with virulence. We conclude that AFLP (discriminatory index = 0.88) has a higher discriminatory power for strain differentiation among S. typhi than ribotyping (DI = 0.63) and PFGE (DI = 0.74). (C) 2000 Elsevier Science B.V. All rights reserved.